The first species of Nemestrinidae (Diptera) endemic to Madagascar: A remarkable new species of Atriadops Wandolleck, 1897 - Barraclough, David A.; Colville, Jonathan F. (Zootaxa, 2022)
A new species of Nemestrinidae, Atriadops irwini Barraclough sp. nov., is described and illustrated from Sakaramy in the far north of Madagascar at about the same latitude as the Comoros Islands. The species was collected in lowland tropical forest by Dr Michael Irwin. Atriadops Wandolleck, 1897, is a small genus of Nemestrinidae in the subfamily Trichopisideinae. Six named species are distributed across the Australasian, Oriental, Afrotropical and Neotropical Regions. Atriadops irwini sp. nov. is thus only the seventh species in the genus (the first new species described in almost 70 years) and the second valid species from the Afrotropical Region. This is the first record of Atriadops from Madagascar, where the new species is the only endemic nemestrinid. Nycterimyia capensis Bezzi is the only other nemestrinid recorded from Madagascar, but it also occurs in South Africa (where it was first described) and Kenya. The world fauna of Atriadops is discussed and all known larval host records are listed.